Surfactant Enhanced Mobilization of Mineral Oil within Porous Media - A. R. Duffield; R. S. Ramamurthy; J. R. Campanelli (Water, Air, & Soil Pollution, 2003)

Genetic evidence for a family structure in stable social aggregations of the Australian lizard Egernia stokesii - M. G. Gardner; C. M. Bull; S. J. B. Cooper; G. A. Duffield (Molecular Ecology, 2001)
In this study we used data from six unlinked microsatellite loci to examine stable aggregations of Egernia stokesii , from a population in the southern Flinders Ranges of South Australia. We show that these aggregations are comprised of breeding partners, their offspring from two or more cohorts, and related adults, providing the first genetic evidence of a family structure in any lizard species. Despite this high level of relatedness within aggregations, most breeding pairs were unrelated and partners were less closely related to each other than they were to other potential within‐group partners. Where individuals dispersed, both sexes usually moved to social groups close to their natal group. Although both sexes showed natal philopatry, there was some evidence that females in groups were more related than males in groups. These data suggest that an active choice of unrelated partners and male‐biased dispersal may be the mechanisms used by E. stokesii to avoid inbreeding within groups.